1982
DOI: 10.1111/j.1529-8817.1982.tb03215.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYSIOLOGY OF SEA ICE DIATOMS. I. RESPONSE OF THREE POLAR DIATOMS TO A SIMULATED SUMMER‐WINTER TRANSITION1

Abstract: Three axenic polar sea ice diatom cultures were subjected to a 30 day simulated summer‐winter transition in which light and temperature were decreased and salinity was increased to mimic seasonal changes previously reported for ice‐covered polar seas. The diatoms responded to these changes by a reduction in cellular metabolism as indicated by: 1) A decline in growth rate and photosynthetic rate; 2) a decrease in cellular ATP; and 3) the storage and subsequent utilization of endogenous carbon reserves. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 36 publications
6
59
0
Order By: Relevance
“…4 Mean maximum NPQ for all species, temperatures and experiments (n = 3), errors are standard deviations maximum rates at around 10°C (Kottmeier and Sullivan 1988;Fiala and Oriol 1990). However, some polar species exhibit significant suppression of metabolic activity at low temperatures and many only exhibit temperature limitation above 5°C (Palmisano and Sullivan 1982;Palmisano et al 1985). Thus, the range of temperatures used in the incubations here may not be outside their physiological acclimation limits.…”
Section: Discussionmentioning
confidence: 99%
“…4 Mean maximum NPQ for all species, temperatures and experiments (n = 3), errors are standard deviations maximum rates at around 10°C (Kottmeier and Sullivan 1988;Fiala and Oriol 1990). However, some polar species exhibit significant suppression of metabolic activity at low temperatures and many only exhibit temperature limitation above 5°C (Palmisano and Sullivan 1982;Palmisano et al 1985). Thus, the range of temperatures used in the incubations here may not be outside their physiological acclimation limits.…”
Section: Discussionmentioning
confidence: 99%
“…These two problems are examined in turn. First, Palmisano and Sullivan (1982) have shown that a slight increase in temperature can dramatically change the algal growth rate. Their division rates at 0°C ranged from 0.26 to 0.29 div d-I, while only 0.13 div d-l or none (according to the species) were recorded at -1.5"C (see their figure 2A-F'), which is the freezing point of seawater of 27.9%0.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the diurnal light-dark rhythm, diatoms store lipids in excess to better cope with unfavorable growth conditions like nutrient limitation (Roessler 1990;Fahl and Kattner 1993), low irradiance and low temperatures (Smith and Morris 1980;Palmisano and Sullivan 1982). Lipid droplets have been detected at high quantities in polar plankton and sea ice diatom taxa in summer and late autumn (Fryxell 1989;Fahl and Kattner 1993;Zhang et al 1998).…”
Section: The Lipids Metabolism Under Darknessmentioning
confidence: 99%
“…In diatoms different mechanisms have been described for long-term dark survival (McMinn and Martin 2013). Those include the utilization of stored energy products (Palmisano and Sullivan 1982), the reduction of metabolic activity (Palmisano and Sullivan 1982), formation of resting stages (Durbin 1978;McQuoid and Hobson 1996), and/or a facultative heterotrophic lifestyle (Lewin and Lewin 1960;Hellebust and Lewin 1977;Tuchman et al 2006). The utilization of energy storage products, such as lipids (triacylglycerol) and carbohydrates (chrysolaminarin), could provide energy for the cellular maintenance metabolism during long periods of darkness.…”
Section: Introductionmentioning
confidence: 99%